Comparison of gases applications to wet and dry cuttings in turning - Çakir, O; Kiyak, M; Altan, E (ELSEVIER SCIENCE SA, 2004)
In recent years, by the progresses in manufacturing industry, great changes have especially been observed in machining of metals. All cutting parameters have already been investigated in order to advancing the properties of cutting tools and machine tools. These researches have improved material removals rate, decreased manufacturing time and resulted minimum cutting energy. The effects of dry and wet cuttings have widely been examined on metal machining. In this study, the effects of cutting fluid, some gases applications and dry cutting on cutting forces, thrust forces, surface roughness, friction coefficient and shear angle have been examined in turning of AISI1040 steel material. Nitrogen, oxygen and carbon dioxide gases instead of cutting fluid have been used and compared to wet and dry machining processes. Experiments have been performed at constant cutting speed for three different cutting depths and feeds. The application of gases produced lower cutting force comparing to dry and wet cutting. The values of surface roughness were slightly closed. Gases applications in turning provided higher shear angle value than dry and wet cutting. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: turning; cutting fluid; cutting force; surface roughness; LUBRICANTS; METAL; Engineering; Materials Science